Institutional Dynamics and Community-Level Religious Governance: A Systems Perspective on Mahayana Buddhist Practice in Rural Indonesia - Sya’ban, Fikri; Ubaidillah, Ubaidillah (3 Issues per year (April, August and December), 2025)
This study examines how Mahayana Buddhist practice is institutionally sustained and governed at the community level within a rural Indonesian context, framing religion as a social system shaped by collective decision processes and informal governance structures. The purpose of the study is to move beyond descriptive accounts of religious existence by analyzing how institutional dynamics, normative authority, and communal coordination interact to maintain religious continuity under local social constraints. Employing a qualitative case-based approach, the study draws on in-depth interviews, participant observation, and document analysis to capture everyday practices, leadership roles, and decision-making mechanisms embedded within the Mahayana Buddhist community. The findings reveal that religious sustainability is not driven by doctrinal enforcement, but by adaptive governance arrangements that balance ethical norms, communal legitimacy, and situational flexibility. Authority is exercised through negotiated roles rather than formal hierarchy, while collective decisions emerge through consensus-oriented processes that integrate religious values with local socio-cultural realities. These dynamics function as an informal yet stable governance system that enables the community to manage internal coordination and external pressures without institutional rigidity. The significance of this study lies in its contribution to systems-oriented perspectives in decision sciences and institutional analysis by demonstrating how religious practice operates as a socially embedded system of governance. By conceptualizing religion as a dynamic decision environment shaped by institutional interaction rather than static belief, the study offers an alternative analytical lens for understanding governance processes in non-state, value-driven systems, thereby extending the relevance of operations and systems research to socio-religious contexts that remain underexplored in international scholarship